2007
DOI: 10.1002/mus.20900
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen for spasticity‐related pain in amyotrophic lateral sclerosis: Efficacy and factors associated with pain relief

Abstract: Clinical signs and symptoms of spasticity include hypertonia, involuntary movements (spasms, clonus), decreased range of motion, contractures, and often spasm-related pain. When spasticity is refractory to medical management, patients may be referred for intrathecal baclofen (ITB) pump placement. We reviewed a cohort of amyotrophic lateral sclerosis (ALS) patients with intractable spasticity requiring ITB to further define the impact of ITB on pain relief in this patient population. From 2003 to 2005, eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…However, as the cramps progress in intensity and duration, carbamazepine, quinine sulphate, or phenytoin may also be given [35]. With time and the development of spasticity, myorelaxants such as baclofen, a γ -amino-butyric acid (GABA) analog that facilitates spinal motor neuron inhibition, are employed [37, 38]. Oral baclofen is usually administered 2-3 times a day in a 10 mg dose, but can be titrated up to a 4 times per day—20 mg dose if necessary [36, 39].…”
Section: Current Als Pain Therapiesmentioning
confidence: 99%
“…However, as the cramps progress in intensity and duration, carbamazepine, quinine sulphate, or phenytoin may also be given [35]. With time and the development of spasticity, myorelaxants such as baclofen, a γ -amino-butyric acid (GABA) analog that facilitates spinal motor neuron inhibition, are employed [37, 38]. Oral baclofen is usually administered 2-3 times a day in a 10 mg dose, but can be titrated up to a 4 times per day—20 mg dose if necessary [36, 39].…”
Section: Current Als Pain Therapiesmentioning
confidence: 99%
“…The average reduction in pain scale was 54% after placement of the pump. 19 The value of exercise in the treatment of spasticity in ALS patients is unclear. One study of a personalized exercise program in the treatment of ALS-related spasticity showed benefit at 3 months, but this was not statistically significant.…”
Section: Painmentioning
confidence: 99%
“…The most recent AAN practice parameter 11 notes that there are no controlled trials on the treatment of depression or anxiety in ALS, although at least one study suggested that depression is treatable even in the end stages of this illness. 19 Choice of antidepressant should be tailored to the patient's symptoms. Tricyclic antidepressants can be used for sialorrhea as well as mood, although the doses required for antidepressant effect are associated with an increased side effect profile compared with other medications.…”
Section: Mood Disorders In Alsmentioning
confidence: 99%
“…Although pain is not typically associated with ALS, its presence can be devastating and is likely multifactorial when it occurs, such as in the setting of prominent spasticity. 41 Identification of distal, symmetric sensory loss in a patient with UMN and LMN symptoms and signs should prompt an evaluation of common causes of sensory neuropathy, including diabetes mellitus, thyroid disease, alcohol abuse, paraproteinemia, paraneoplastic disease, connective tissue disease, vitamin B12 deficiency, and copper deficiency. In a patient who has an LMN syndrome beginning in the bulbar region and proximal upper extremities, and who has abnormal sensory nerve conduction studies, X-linked recessive bulbospinal neuronopathy (Kennedy's disease) 42 should be considered.…”
Section: Sensory Abnormalitiesmentioning
confidence: 99%